2015
DOI: 10.1590/1807-3107bor-2015.vol29.0095
|View full text |Cite
|
Sign up to set email alerts
|

Individual and contextual determinants of malocclusion in 12-year-old schoolchildren in a Brazilian city

Abstract: The aim of this study was to describe malocclusion prevalence and its association with individual and contextual factors among Brazilian 12-year-old schoolchildren. This cross-sectional study included data from an oral health survey carried out in Goiânia, Brazil (n = 2,075), and data from the files of the local health authority. The data were collected through oral clinical examinations. The Dental Aesthetic Index (DAI) was used to assess occlusion. The presence of malocclusion (DAI > 25) was used as the depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
1
10
1
5
Order By: Relevance
“…In 2010, there was an occurrence of malocclusions were 38.8% at the age of 12 years old. Our results are near to the related by Jordão who found a prevalence of 40.1%, when examined 2.075 Brazilian people aged 12 years old . Higher prevalence were found in other studies, such as in a systematic review in Iran population (54.6%) and in a cross‐sectional study that included 2366 Indian students aged 10‐12 years old (83.3%) …”
Section: Discussioncontrasting
confidence: 50%
“…In 2010, there was an occurrence of malocclusions were 38.8% at the age of 12 years old. Our results are near to the related by Jordão who found a prevalence of 40.1%, when examined 2.075 Brazilian people aged 12 years old . Higher prevalence were found in other studies, such as in a systematic review in Iran population (54.6%) and in a cross‐sectional study that included 2366 Indian students aged 10‐12 years old (83.3%) …”
Section: Discussioncontrasting
confidence: 50%
“…Eğitim seviyesi yüksek olan ailelerin, maloklüzyon ile ilgili daha fazla bilgiye sahip oldukları ve çocukların oklüzyonları üze-rinde koruyucu etkilerinin olduğu bildirilmiştir. 54 Bu aileler, çocuklarının ağız ve diş sağlığı ile ilgili olarak daha fazla endişe duymakta ve ortodontik tedavi ihtiyaçlarını rahatlıkla algılayabilmektedir-ler. Bu nedenlerden dolayı da, eğitim düzeyi yük-sek aileler günümüzde koruyucu tedavilerden (florid uygulamaları ve fissur örtücüler) daha fazla yararlanmakta ve maloklüzyon ile sonuçlanabile-cek diş problemleri ile ilgili erken önlemlerin alın-ması için diş hekimlerine düzenli olarak daha çok başvurmaktadırlar.…”
Section: Ai̇leni̇n Eği̇ti̇m Durumu İle Ortodonti̇k Tedavi̇ İhti̇-yaci Arasinunclassified
“…In general, individuals with low socioeconomic status suffer greater degrees of oral problems 9,10 . Previous studies have shown that adolescents from low-income families whose parents have a lower level of schooling have a higher prevalence of malocclusion 6,11,12 . However, this association remains controversial, as some studies have not identified this relationship 1,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…A Brazilian study evaluated the association between malocclusion in 12-year-old childrenand individual and contextual factors and found that individuals from sanitation districts with worse conditions of basic sanitation, housing, family income and schooling had a higher prevalence of malocclusion 12 . A nationwide Brazil-based study showed that 12-year-old children living in cities where more families were dependent on government social benefits, which had a lower gross domestic product, and which performed worse in terms of population health care, had higher prevalences of malocclusion 6 .…”
Section: Introductionmentioning
confidence: 99%